Effect of Oat Hay as a Substitute for Alfalfa Hay on the Gut Microbiome and Metabolites of Yak Calves - Yingchao Gu; Lele An; Yanan Zhou; Guoliang Xue; Yang Jiao; Deyu Yang; Shujie Liu; Zhanhong Cui (Animals)
To evaluate the impact of different roughages on the intestinal microbiota of yak calves, we fed them oat hay in substitution of alfalfa hay, in addition to milk replacer and starter powder. Twenty-one 45-day-old male yak calves were selected and randomly assigned to three groups: the milk replacer + starter + alfalfa hay group (AH), the milk replacer + starter + oat hay group (OH), and the milk replacer + starter + mixed hay group (AO), in which the alfalfa hay and oat hay were administered in a 1:1 ratio. All calves in the three groups were fed the same milk replacer and an equivalent amount of dry matter. The formal experiment commenced after a 21-day pre-test period and lasted for 120 days. Following the experiment, the contents of the jejunum and colon were collected to investigate the intestinal microbiota and metabolites using 16S rRNA sequencing and LC-MS metabolomics. The result showed that the AO group had greater final body weights overall than the AH group and OH group (p < 0.05). The AH group and OH group had considerably greater feed-to-gain ratios than the AO group (p < 0.05). At the phylum level, the OH group exhibited an increased relative abundance of Bacteroidota and Spirochaetota in the jejunum (p < 0.05). The relative abundance of Actinobacteriota in the colon was increased in the AO group (p < 0.05). At the genus level, the AO group exhibited a decreased abundance of Clostridium sensu_stricto_1 (p < 0.05), and the OH group showed an increased abundance UCG-005 and Alistipes in the jejunum. There were many differential metabolites in the OH group and AO group compared to the AH group, and the different metabolites of the OH group were associated with the metabolic pathways of the nervous system, sensory system, amino acid metabolism, and lipid metabolism in the jejunum and with lipid metabolism, amino acid metabolism, and the nervous system in the colon. In the AO group, these metabolites were associated with the digestive system and the translation and metabolism of cofactors in the jejunum and with the metabolism of cofactors and vitamins in the colon. In summary, it is feasible to replace alfalfa hay with oat hay based on milk replacer and starter. The combination of the two forages enhanced nutrient absorption, improved immune function, maintained the internal homeostasis of yak calves, and was more beneficial to their growth and development.